Supplementary Figure S1 from Clinical Features Associated with Outcomes and Biomarker Analysis of Dabrafenib plus Trametinib Treatment in Patients with BRAF-Mutant Melanoma Brain Metastases - James S. Wilmott (15008931) (2025)
Gene expression of major signalling pathways and multiplex immunohistochemical comparison of markers between timepoints and tumor sites. A) Gene expression of related oncogenic signalling pathways between treatment timepoints and site, B) Estimated mean difference of proteins and pathways between biopsy categories (95% confidence interval for the estimated mean difference is depicted as a segment), C) Multiplex immunohistochemical staining for key intracellular signalling proteins, D) Changes in immune intratumoral immune cell densities between treatment timepoints and site, E and F) Multiplex immunohistochemical staining depicted marked decrease in immune cell densities EDT in PT4 (steroid treated). PRE, collected prior to treatment; EDT, collected early during treatment (i.e., after 10-14 days of dabrafenib). MBM, melanoma brain metastasis; ECM, extracranial metastasis. PT, patient.